Are we neglecting sexual function assessment in suspected cauda equina syndrome?. Issue 1 (February 2020) - Pronin, Savva; Hoeritzauer, Ingrid; Statham, Patrick F.; Demetriades, Andreas K.
Abstract: Objectives: We assessed the documentation rates of signs and symptoms, including sexual function, in patients with suspected cauda equina syndrome and whether they can be improved by increasing local awareness. Patients and methods: We reviewed all electronic records of patients referred with suspected CES who required urgent MRI to our regional service over a 2 month period. We recorded the documentation rates of clinical signs and symptoms. The results were presented locally to increase awareness. A further 2 month period was then re-audited. 120 patients in total were included across both time periods. Chi-squared was used to compare documentation rates between time periods. Results: 25 of 120 patients had radiological cauda equina compression. Lower limb neurology, urinary function and saddle sensation were almost universally documented. After the intervention, there was a significant increase (p < 0.05) in the documentation of bowel function and post-void residual but not sexual function. Sexual function was poorly documented with rates of 3% and 11% throughout the two audited periods. Conclusion: Certain clinical features of CES are well documented. Increasing awareness may improve documentation of certain symptoms/signs in patients with suspected cauda equina syndrome. Sexual function was poorly documented and increasing awareness alone is an inadequate intervention.